INNOVATION ASSISTANCE IN MANUFACTURING FERMENTED ELEPHANT GRASS AS CATTLE FEED IN BREMI VILLAGE, PROBOLINGGO DISTRICT - Ahmad Patih; Amsori; Hasan Ansori; Loviga Denny Pratama (Najah: Journal of Research and Community Service, 2023)
Most of the people in Bremi Village have dairy farming businesses. However, some of them are still confused about the nutrition for their cattle. So innovation is needed regarding cow food in the village. The aim of this program is to provide knowledge to farmer groups so they can improve their skills in making fermented elephant grass for animal feed. The method used is the ABCD (Asset-Based Community-Development) method. This outreach was carried out by providing material and practice to farmer groups regarding how to make fermented elephant grass. This material introduces the materials and tools used in the fermentation process, the benefits of fermented elephant grass, the nutritional quality of elephant grass, and techniques for processing fermented elephant grass. The results of the activity evaluation show that community knowledge, especially the livestock breeder group, which initially still had minimal knowledge regarding elephant grass fermentation, has increased quite well after the socialization was held. So it can be concluded that apart from implementing the tri dharma of higher education, this community service also helps government programs in encouraging the productivity of dairy farmers in Bremi Village.